5y-5=3y+1

Simple and best practice solution for 5y-5=3y+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5y-5=3y+1 equation:


Simplifying
5y + -5 = 3y + 1

Reorder the terms:
-5 + 5y = 3y + 1

Reorder the terms:
-5 + 5y = 1 + 3y

Solving
-5 + 5y = 1 + 3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3y' to each side of the equation.
-5 + 5y + -3y = 1 + 3y + -3y

Combine like terms: 5y + -3y = 2y
-5 + 2y = 1 + 3y + -3y

Combine like terms: 3y + -3y = 0
-5 + 2y = 1 + 0
-5 + 2y = 1

Add '5' to each side of the equation.
-5 + 5 + 2y = 1 + 5

Combine like terms: -5 + 5 = 0
0 + 2y = 1 + 5
2y = 1 + 5

Combine like terms: 1 + 5 = 6
2y = 6

Divide each side by '2'.
y = 3

Simplifying
y = 3

See similar equations:

| 4x-0.04x^3=0 | | -2w=w+12 | | Rx=(400+20x)(90-1x) | | 42+p=95 | | 14s-20= | | 5n-12=n+18+9n | | 2(x+3)(x+8)= | | Rx=(400+20x)(90+-1x) | | -8+3(2p-4)+10p= | | y*.3=2.5 | | -2(4+3c)-8= | | 12=z | | (4+u)(5u-2)=0 | | 5x-20=3x+15 | | 9y^2+66y+122=0 | | x*.3=2.5 | | 10a+3(a+2)= | | (2v-7)(5-v)=0 | | 5(x+7)+4x^2=(x+5)(x+7) | | 3sin(x)+2cos(x)=0 | | 10x+[2+8x]=4 | | 4x^3-2xy= | | 2.5=11.50 | | 28=8+2x | | -2t-5= | | -53+12X=115 | | 9x-2[x+4]=34 | | Ln(4x-7)=ln(x+5) | | -63=-27-3X | | y+5.8=1.34 | | x+(-12)=112 | | (h^3-2h)+(3h^2+4h)-2h^3= |

Equations solver categories